Environmental assessment of a combined heat and power plant configuration proposal with post-combustion CO2 capture for the Mexican oil and gas industry - Morales-Mora, M. A.; Pretelín-Vergara, C. F.; Martínez-Delgadillo, S. A.; Iuga, C.; Nolasco Hipolito, Cirilo (Springer Nature, 2018)
Combined heat and power (CHP) plants retrofitted with post-combustion carbon capture (PCC) are discussed for the Mexican oil and gas industry using a life cycle assessment. This work investigates the energy efficiency improvements and potential environmental impacts generated by a 144-MW CHP plant coupled with PCC in a petrochemical complex. The project considers a change from the current steam-turbine generators (case 1), with an efficiency of 58%, to a gas turbine (case 2) coupled to a heat recovery steam generator to reach a combined efficiency of 87%. We also investigated the PCC of flue gas from the gas turbine in case 2 by chemical absorption using Aspen HYSYS (case 3). The results showed that case 2 leads to a reduction in all evaluated categories of environmental impact when compared to the base case (case 1). The average global warming potential (GWP) is 626 kgCO2eq/MWh for case 1 and 460 kgCO2e/MWh for case 2. In case 3, the GWP of 42 kg CO2e/MWh was estimated, 1075 t/day of CO2 can be captured with a recovery efficiency of approximately 95%, and an energy return of 85% can be obtained. This study provides a new approach for obtaining maximum energy flux with low-carbon emissions, constituting “clean energy” production.
Keywords: Captura de CO2; Turbina de gas; Evaluación del ciclo de vida; Simulación de procesos